Connecting with communities a sourcebook on public journalism - Pabico, Alecks P. (Evelio Javier Foundation, 2001)
Purpose: "...to provide a sort of road map for journalists wishing to expand their coverage, add depth to their news perspective, and begin to write the kind of stories that could help transform communities into self-determining ones."